Operations and supply management : - Jacobs, F. Robert. (McGraw - Hill, 2008)
This book is about designing and operating processes that deliver a firm's goods and services in a maner that matches customer's expectations. Really successful firms have a clear and unambiguous idea of how thay intend to make money.